Predictors of delinquency among adolescents and young adults: a new psychosocial control perspective - Curcio, Angela L. (The Australian and New Zealand journal of criminology, 2017)
The present study examined whether a new psychosocial control model of youth problem behaviours, including additional variables of sensation seeking and peer risk-taking behaviour, could be expanded to explain delinquency in early and mid-late adolescence, and emerging early- and mid-young adulthood. We also explored the possible mediating role of peer risk-taking behaviours on conventional social control risk factors of parent attachment, school connectedness, and perceived seriousness of risk-taking behaviours with delinquency. Using a recently updated Australian self-report delinquency measure that can capture undetected antisocial behaviour among both adolescents and adults, a sample of 329 secondary school students (age groups 13-14 and 15-17, 50.6% female) and 334 university students (age groups 18-20 and 21-24, 68.4% female) in Canberra, Australia participated. The new psychosocial control model explained variance in delinquency with medium to large effect sizes, and beyond the original psychosocial control variables in all four age cohorts. Peer risk-taking behaviour explained the largest proportion of variance across all four age groups; its mediating role was partially supported. Impulsivity predicted delinquency among 13-20 years olds as did sensation seeking among 15-24 years olds, suggesting different, yet overlapping influences on developmental trajectories of delinquency.